Improved visibility of colorectal flat tumors using image‐enhanced endoscopy. (April 2015) - Oka, Shiro; Tamai, Naoto; Ikematsu, Hiroaki; Kawamura, Takuji; Sawaya, Manabu; Takeuchi, Yoji; Uraoka, Toshio; Moriyama, Tomohiko; Kawano, Hiroshi; Matsuda, Takahisa
Abstract : Colonoscopy is considered the gold standard for detecting colorectal tumors; however, conventional colonoscopy can miss flat tumors. We aimed to determine whether visualization of colorectal flat lesions was improved by autofluorescence imaging and narrow‐band imaging image analysis in conjunction with a new endoscopy system. Eight physicians compared autofluorescent, narrow‐band, and chromoendoscopy images to 30 corresponding white‐light images of flat tumors. Physicians rated tumor visibility from each image set as follows: +2 (improved), +1 (somewhat improved), 0 (equivalent to white light), −1 (somewhat decreased), and −2 (decreased). The eight scores for each image were totalled and evaluated. Interobserver agreement was also examined. Autofluorescent, narrow‐band, and chromoendoscopy images showed improvements of 63.3% (19/30), 6.7% (2/30), and 73.3% (22/30), respectively, with no instances of decreased visibility. Autofluorescence scores were generally greater than narrow‐band scores. Interobserver agreement was 0.65 for autofluorescence, 0.80 for narrow‐band imaging, and 0.70 for chromoendoscopy. In conclusion, using a new endoscopy system in conjunction with autofluorescent imaging improved visibility of colorectal flat tumors, equivalent to the visibility achieved using chromoendoscopy.